A novel tertiary interaction in M1 RNA, the catalytic subunit of Escherichia coli RNase P. - Tallsjö, A (1993)
Phylogenetic covariation of the nucleotides corresponding to the bases at positions 121 and 236 in Escherichia coli RNase P RNA (M1 RNA) has been demonstrated in eubacterial RNase P RNAs. To investigate whether the nucleotides at these positions interact in M1 RNA we introduced base substitutions at either or at both of these positions. Single base substitutions at 121 or at 236 resulted in M1 RNA molecules which did not complement the temperature-sensitive phenotype associated with rnpA49 in vivo whereas wild-type M1 RNA or the double mutant M1 RNA, with restored base-pairing between 121 and 236, did. In addition, wild-type and the double mutant M1 RNA were efficiently cleaved by Pb++ between positions 122 and 123 whereas the rate of this cleavage was significantly reduced for the singly mutated M1 RNA variants. From these data we conclude that the nucleotides at positions 121 and 236 in M1 RNA establish a novel long-range tertiary interaction in M1 RNA. Our results also demonstrated that this interaction is not absolutely required for cleavage in vitro, however, a disruption resulted in a reduction in cleavage efficiency (kcat/Km), both in the absence and presence of C5.